2017
DOI: 10.5020/18061230.2017.p239
|View full text |Cite
|
Sign up to set email alerts
|

Percepção dos profissionais de saúde e gestores sobre a atenção em hanseníase na Estratégia Saúde da Família

Abstract: Este artigo publicado em acesso aberto (Open Access) sob a licença Creative Commons, que permite uso, distribuição e reprodução em qualquer meio, sem restrições, desde que o trabalho seja corretamente citado.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
1
0
3

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 19 publications
1
1
0
3
Order By: Relevance
“…The deficits in knowledge and attitude about aspects related to leprosy found in the pre-intervention can also be verified in other studies ( 7 , 15 16 ) , which reported presence of failures and inconsistencies between what is recommended by the MS and what is actually being carried out in PHC to control the isease in the country, which can reverberate in the emergence of complications due to the late inclusion of preventive measures.…”
Section: Discussionsupporting
confidence: 61%
“…The deficits in knowledge and attitude about aspects related to leprosy found in the pre-intervention can also be verified in other studies ( 7 , 15 16 ) , which reported presence of failures and inconsistencies between what is recommended by the MS and what is actually being carried out in PHC to control the isease in the country, which can reverberate in the emergence of complications due to the late inclusion of preventive measures.…”
Section: Discussionsupporting
confidence: 61%
“…A hanseníase, ainda hoje, é uma patologia que há muito preconceito na sociedade. Homens e mulheres sentem vergonha de dizer que apresentam hanseníase, outros infectados relatam desconforto em relação à aparência e aos defeitos neurais que o bacilo pode causar e outros ainda não se sente confiantes em relatar o caso para a família (GIRÃO NETA et al, 2017). Sendo assim, muitos infectados que iniciam o tratamento não se sentem amparados pela família/amigos, tendo por fim o abandono do tratamento e No quesito de gênero, segundo a distribuição de casos, o sexo masculino foi o principal sexo acometido pela doença, o que condiz com a literatura brasileira, já que a nível mundial as mulheres são mais afetadas.…”
Section: Discussionunclassified
“…Dessa forma, muitos casos não são definidos por ausência de espessamento do nervo, dor no nervo acometido, paresia, parestesia e outras manifestações neurológicas, já que o bacilo de Hansen acomete o sistema nervoso periférico (GIRÃO NETA et al, 2017). No que tange a manifestação clínica nervosa tardia, em último caso, há a diminuição da força muscular inervados pelos nervos comprometidos, sendo feito, em muitos casos, o diagnóstico definitivo.…”
Section: Discussionunclassified
See 1 more Smart Citation
“…However, despite the frequent publication of manuals, guidelines, and national and international protocols to guide health professionals' conduct regarding disabilities, studies indicate the presence of gaps in the training of Primary Care (PC) professionals in the management of the disease, among them: long and conflicting therapeutic itinerary to identify signs and symptoms (4) , unpreparedness to proceed with the evaluation of the DPD (5) , and lack of knowledge on the scope of activities related to its prevention and control (6) .…”
Section: Introductionmentioning
confidence: 99%